2011
DOI: 10.1073/pnas.1116227108
|View full text |Cite
|
Sign up to set email alerts
|

An impaired mitochondrial electron transport chain increases retention of the hypoxia imaging agent diacetylbis(4-methylthiosemicarbazonato)copper II

Abstract: Radiolabeleddiacetylbis4-methylthiosemicarbazonatocopper II [Cu II atsm] is an effective positron-emission tomography imaging agent for myocardial ischemia, hypoxic tumors, and brain disorders with regionalized oxidative stress, such as mitochondrial myopathy, encephalopathy, and lactic acidosis with stroke-like episodes (MELAS) and Parkinson's disease. An excessively elevated reductive state is common to these conditions and has been proposed as an important mechanism affecting cellular retention of Cu from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
123
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 42 publications
(44 reference statements)
3
123
2
Order By: Relevance
“…Differences in expression or activity of the heavy metal exporter ATP7B or a dual-phase uptake mechanism have been suggested to have a role in the cell line dependence of 64 Cu-ATSM redistribution (20)(21)(22)(23)(24). However, other factors, such as pH changes, oxidative stress, and the activity of the mitochondrial electron transport chain, seem to influence the cellular trapping of 64 Cu-ATSM (25).…”
mentioning
confidence: 99%
“…Differences in expression or activity of the heavy metal exporter ATP7B or a dual-phase uptake mechanism have been suggested to have a role in the cell line dependence of 64 Cu-ATSM redistribution (20)(21)(22)(23)(24). However, other factors, such as pH changes, oxidative stress, and the activity of the mitochondrial electron transport chain, seem to influence the cellular trapping of 64 Cu-ATSM (25).…”
mentioning
confidence: 99%
“…The mechanism responsible for 64 Cu-ATSM retention is not completely understood, but in vitro studies have indicated that the 64 Cu-ATSM complex undergoes reduction by free diffusion after entering the cells (27)(28)(29). In normoxic cells, 64 Cu-ATSM is rapidly reoxidized and consequently able to leave the cell again by free diffusion.…”
mentioning
confidence: 99%
“…Thus, 62 Cu-ATSM is retained in sites with an over-reductive state in the delayed phase (10–20 min) [7, 18-20]. A higher accumulation of Cu-ATSM observed in cell lines with increased levels of biological reductant NADH due to hypoxia or mitochondrial respiratory failure than that in the parental cells under normoxic conditions supports the retention mechanism of this ligand [8, 21, 22]. …”
Section: Discussionmentioning
confidence: 86%